Women achieve peak freestyle swim speed at earlier ages than men - Rüst, C. A.; Knechtle, B.; Rosemann, T. (Open Access Journal of Sports Medicine, 2012)
The age of peak swim performance has been investigated for freestyle swimmers for distances ranging from 50 m to 1500 m among swimmers aged 19 to 99 years. However, studies have yet to investigate the 10 to 19 year-old age group. The aims of the present study were (1) to investigate the age range of peak freestyle swim speed, and (2) to find differences in age range and peak freestyle swim speed between male and female freestyle swimmers from 50 m to 1500 m at a national level. Methods: The changes in age range and peak freestyle swim speed among Swiss elite freestyle swimmers aged 0-9 years and 70-79 years who were ranked on the Swiss high score list between 2006 and 2010 were analyzed using linear regression analyses and analysis of variance. Results: Men were fastest at ages 22-23 years for 100 m and 200 m; at ages 24-25 years for 400 m and 800 m; and at 26-27 years for 50 m and 1500 m. Women achieved peak freestyle swim speed at ages 20-21 years for all distances with the exception of 800 m. In the 800 m, women were fastest at ages 26-27 years. The difference in peak freestyle swim speed decreased with increasing swim distance from 50 m to 800 m (ie, 13.1% ± 1.3% in 50 m; 13.2% ± 0.9% in 100 m; 10.8% ± 0.9% in 200 m; 7.9% ± 1.3% in 400 m; and 4.2% ± 2.0% in 800 m). For 1500 m, however, the gender difference increased to 6.4% ± 2.3%. Conclusion: These findings suggest that peak freestyle swim speed is achieved at lower age ranges in women when compared to men at 50 m to 1500 m, but not at 800 m. The gender difference in peak freestyle swim speed decreased with increasing swim distance from 50 m to 800 m, but not for 1500 m. These data should be confirmed with swimmers at an international level.